Study guides

☆☆

Q: 5x plus y equals 1 3x plus 2y equals 2?

Write your answer...

Submit

Still have questions?

Related questions

If: 3x+2y = 5x+2y = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtract the 1st equation from the 2nd equation: 2x = 0 or x = o By substitution: x = 0 and y = 3.5

If: 3x+2y = 5x+2y = 14 Then: 3x+2y = 14 and 5x+2y =14 Subtract the 1st equation from the 2nd equation: 2x = 0 Therefore by substitution the solutions are: x = 0 and y = 7

(1, 0)

If: 3x+2y = 5x+2y = 7 which is the same as 7 = 7 = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtracting equations: x = 0 Therefore by substitution: x = 0 and y = 3.5

(3, -4)

For 5x+y=1, you would subtract 5x from each side, so you would get y=1-5x For 3x+2y=2, you would subtract 3x from each side, and then divide by 2. 2y=2-3x y=1-(3/2)x

3x+2y=20 5x-2y=1 (3x+2y) + (5x-2y)= 20+1 3x+5x= 21....... 8x=21.........x=2 5/8 Subsitute x=3(2 5/8)+ 2y=20........... 7 7/8 +2y=20.........2y= 20- 7 7/8....... y=6 1/16

Both of them are equations!The solution is (x, y) = (2, 1).

5x-2y+3z-2x-y-4z=3x-3y-z

(3x+2y)*(5x-3y) =3x*5x + 3x*(-3y) + 2y*5x + 2y*(-3y) [This is sometimes called the FOIL method - You multiply the First members of each bracket, then the Outers, Inners, Lasts] = 15x2 - 9xy + 10xy - 6y2 = 15x2 + xy - 6y2

If you mean: 2y+5x = 13 and 2y-3x = 5 then x = 1 and y = 4

In its simplest form: 2y -5x

People also asked